A National Survey of EMR Usability: Comparisons between medical and nursing professions in the hospital and primary care sectors in Australia and Finland. (October 2021) - Lloyd, Sheree; Long, Karrie; Oshni Alvandi, Abraham; Di Donato, Josie; Probst, Yasmine; Roach, Jeremy; Bain, Christopher
Highlights: Usability can be measured in the Australian context using the NuHISS developed by Finnish researchers. Impressions differ between nurses and medical professionals in relation to EMR usability. Impressions vary within professional groups and across sectors in the Australian context. Comparisons between countries are difficult as contexts where clinicians practice and EMR systems differ. Abstract: Background: Electronic Medical Record Systems (EMRs) are now part of nursing and medical professionals daily work in the acute and primary care sectors in Australia. Usability is an important factor in their successful adoption and impacts upon clinical workflow, safety and quality, communication, and collaboration. This study replicates a significant body of work conducted by Finnish researchers applying a usability focused survey to understand medical and nursing professionals' experiences in the Australian context. As we implement EMRs across health systems, their usability and design to support clinicians to effectively deliver and document care, is essential. Methods: We conducted an observational study using a cross sectional survey, the National Usability-Focused HIS Scale (NuHISS) developed and validated by Finnish researchers. For this study 13 usability statements collected clinician impressions of EMRs related to technical quality, ease of use, benefits, and collaboration. We report the responses from medical and nursing professionals working in clinical practice settings in Australia, including primary care and hospital sectors in 2020. Results: Nursing and medical professionals have different experiences with EMR usability. This depends on the sector they work in and the usability feature measured. In our sample, technical quality features were more positively experienced by doctors in the primary care sector than nurses as well as ease of obtaining patient information and prevention of errors. In the hospital sector nurses experiences with EMRs were more positive with respect to support for routine task completion, learnability, ease of obtaining patient information and entry of patient data. Conclusions: The NuHISS is a suitable tool for measuring the usability experiences of Australian clinicians and the EMRs utilised. Differences in usability experiences were noted between professional groups and sectors. A focus on the usability perspectives of clinicians when enhancing or developing EMR solutions is advocated.